42.3k views
5 votes
Solve the system using a matrix,
3x – 2y = 2
6x - 5y = -1

User Mromer
by
6.0k points

1 Answer

4 votes

9514 1404 393

Answer:

(x, y) = (4, 5)

Explanation:

The solution to the matrix equation ...


\left[\begin{array}{cc}3&-2\\6&-5\end{array}\right] \left[\begin{array}{c}x\\y\end{array}\right] =\left[\begin{array}{c}2\\-1\end{array}\right]

is shown in the attachment. It is found by multiplying the equation on the left by the inverse of the coefficient matrix.


\left[\begin{array}{c}x\\y\end{array}\right] =\left[\begin{array}{c}4\\5\end{array}\right]

Solve the system using a matrix, 3x – 2y = 2 6x - 5y = -1-example-1
User Jerry Tian
by
5.1k points